The Influence of Financial Literacy and Entrepreneurial Spirit on the Welfare of Weaving Craftsmen in Bali - A.A Ketut JAYAWARSA; Komang Adi Kurniawan SAPUTRA (PT Keberlanjutan Strategis Indonesia, 2026)
This study analyzes the influence of financial literacy and entrepreneurial spirit on the welfare of ate weavers in Karangasem Regency, Bali. Using multiple regression methods, data were collected from 95 respondents who were ate weavers. The results of the analysis show that financial literacy has a positive and significant influence on welfare with a coefficient of 0.45 (p-value <0.01), while entrepreneurial spirit also contributes positively with a coefficient of 0.35 (p-value <0.05). The research model explains 62% of the variation in the welfare of craftsmen. These findings indicate that increasing financial literacy and entrepreneurial spirit can improve the welfare of ate weavers. Therefore, training programs in both aspects are highly recommended to support local economic growth and community welfare.